[3+2]-Annulation of platinum-bound azomethine ylides with distal C[double bond, length as m-dash]C bonds of N-allenamides - Chakrabarty, Indradweep; Inamdar, Suleman M.; Akram, Manjur O.; Gade, Amol B.; Banerjee, Subhrashis; Bera, Saibal; Patil, Nitin T. (Chemical Communications, 2017)
A Pt-catalyzed, highly regioselective reaction between N-allenamides and imino-alkynes leading to pyrrolo[1,2-a] indoles is described. This represents the first example of [3+2]-annulation of Pt-bound azomethine ylides with the distal CQC bond of N-allenamides. The mechanism of the reaction was established by computational studies.